EFFECT OF METHIMAZOLE-INDUCED HYPOTHYROIDISM ON HISTOLOGICAL CHARACTERISTICS OF PAROTID GLAND OF ALBINO RAT - Hayat, Hayat NQ; Tahir, Tahir M; Munir, Munir B; Sami, Sami W (Journal of Ayub Medical College Abbottabad, 2010)
Background: The current study was carried out to investigate the effect of hypothyroidism on the histological structure of parotid salivary gland of the rat. Methods: Twenty male albino rats, weighing between 130-150 grams, were used which were divided into two groups; control group (A) and an experimental group (B), each containing 10 animals. Group B was rendered hypothyroid by giving methimazole (MMI) as 0.02% solution in drinking water daily for 3 weeks. On day 22nd parotid and thyroid glands were removed, weighed and processed for light microscopy. Salivary gland was fixed in Bouin’s solution, H&E and Toluidine blue stains were used for histological examination. Serum T3, T4 and TSH levels were determined by enzyme immunoassay. Results: In group A, serum concentration of T 3, T4 and TSH was 12.58±3.05 Î·g/ml, 4.72±1.20 µg/dl, and 0.25±0.24 µIU/ml respectively, where as in group B it was 2.14±1.83 Î·g/ml, 1.04±0.44 µg/dl and 1.44±0.20 µIU/ml respectively. When differences between T3, T4 and TSH of the groups were compared, the p-value was <0.000, <0.000, and <0.000 respectively. Mean thyroid weight significantly increased in group B (44.1 0±1.66 mg) when compared to that in group A (33.70±1.56 mg). These findings established the occurrence of hypothyroid state in the experimental group. There was a statistically significant reduction in the parotid gland weight in the animals of the experimental group (38.30±1.15 mg) when compared to the control group (39.60±0.84 mg), (p<0.01). With light microscopy, group A showed a normal structure of parotid salivary gland, whereas multiple histological changes were observed in parotrid gland of the experimental group. Number of mast cells in parotid gland was also significantly higher (p<0.017) in group B (3.70±1.11/mm2) than in group A (2.25±1.34/mm2). Conclusion: The level of T3, T4 decreased and that of TSH increased in the experimental group when compared with control group; there were also changes in the histological structure of the parotid salivary gland. Keywords: Methimazole, parotid gland, hypothyroidism, histology, rat